Social intelligence of cadets of the security and defence sector higher education institutions who receive higher education in the specialities of “Law” and “Psychology” (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article emphasises that for the actors of the security and defence sector, solving various communication situations is a constant and important task which can become difficult to perform if the social intelligence abilities are not sufficiently developed.A comparative analysis of the peculiarities of social intelligence abilities of higher education students of higher education institutions of the security and defence sector, who study in the specialities of “Law” and “Psychology”, was carried out. It is emphasized that the specificity of the social situation of the study participants' intellectual abilities development is due to certain features: lockdowns and quarantines of 2020–2021 with the vast majority of distance education, which were caused by the spread of the COVID-19 virus infection; martial law, which has been in force since February 2022.The senior students of Kharkiv National University of Internal Affairs and the Military Law Institute of Yaroslav Mudryi National Law University took part in the study. The empirical data were obtained using J. Guilford’s psychodiagnostic methodology for studying social intelligence.It has been found that the general level of social intelligence of most of the surveyed cadets corresponded to the average level. It has been shown that the general level of social intelligence of the cadets studying “Psychology” was higher than that of the cadets studying “Law”. It has been revealed that the differences in the level of social intelligence of the surveyed groups of cadets were due to a statistically significantly higher level of development of the ability to predict the consequences of the behaviour of others in typical conditions among cadets studying “Psychology” and a more developed ability to understand the logic of interaction situations and the significance of people's behaviour in these situations. It has been established that the most developed ability of social intelligence of the study participants studying in the speciality “Law” was the ability to understand the change in the meaning of similar verbal reactions of a person depending on the context of the situation that caused them.It has been argued that the specific social conditions of personality formation of higher education students in recent years have not significantly affected the level of development of their social intelligence abilities. The main directions of development of social intelligence abilities of cadets studying in different specialities are presented.